2016
DOI: 10.1111/pbi.12637
|View full text |Cite
|
Sign up to set email alerts
|

The expression of heterologous Fe (III) phytosiderophore transporter HvYS1 in rice increases Fe uptake, translocation and seed loading and excludes heavy metals by selective Fe transport

Abstract: SummaryMany metal transporters in plants are promiscuous, accommodating multiple divalent cations including some which are toxic to humans. Previous attempts to increase the iron (Fe) and zinc (Zn) content of rice endosperm by overexpressing different metal transporters have therefore led unintentionally to the accumulation of copper (Cu), manganese (Mn) and cadmium (Cd). Unlike other metal transporters, barley Yellow Stripe 1 (HvYS1) is specific for Fe. We investigated the mechanistic basis of this preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 67 publications
0
36
0
Order By: Relevance
“… 110 This has so far not been a problem, for example overexpression of barley Yellow Stripe 1 ( HvYS1 ) led specifically to increases in iron. 111 …”
Section: Biofortification Of Crops With Ironmentioning
confidence: 99%
“… 110 This has so far not been a problem, for example overexpression of barley Yellow Stripe 1 ( HvYS1 ) led specifically to increases in iron. 111 …”
Section: Biofortification Of Crops With Ironmentioning
confidence: 99%
“…Therefore, the heterologous expression of the pcaA gene will be able to increase the cadmium tolerance of fungal strains with bioremediation and biomining potential, and this approach may represent an attractive future strain improvement strategy when the application of living fungal biomass is considered in various environmental biotechnological processes. Moreover, our results also suggest that strategies based on the inhibition of cadmium uptake by plants can be efficiently combined with strategies aimed at increasing the cadmium efflux of plant cells to prevent the accumulation of this toxic metal in crops.…”
Section: Discussionmentioning
confidence: 67%
“…However, in plants, Cd 2+ enters root cells predominantly via Fe 2+ transporters, for example through OsIRT1 and OsNRAMP5 in rice . The upregulation of iron transport mechanisms specific to iron but not to cadmium—for example (phyto)siderophore‐mediated iron transport or certain metal transporters—can reduce cadmium uptake by reducing the activity of iron transporters also used by Cd 2+ . Therefore, the observed correlation between the ability for TAF‐C production and for growth in the presence of CdCl 2 in A. fumigatus (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In an early study using constitutive expression of barley YS1 in rice, plants showed superior growth in alkaline soil conditions but did not contain significantly more iron in grains (Gomez-Galera et al, 2012). Later, barley YS1 expressed in rice was shown to promote the preferential mobilization and loading of Fe in seeds while displacing Cd and Cu (Banakar et al, 2017). At present, two key uptake genes, Ys1 and Ys3 ( TOM1 ), for the grass specific mechanism are understood, as are the genes involved in PS synthesis, but it is unclear whether additional grass specific components exist.…”
Section: Discussionmentioning
confidence: 99%